Bilateral White and black in the poetry of Antar bin Shaddad al-Absi (Raparin Journal of Humanities (RJH), 2020)
The importance of this research is that it goes beyond the many descriptive studies that dealt with pre-Islamic poetry and poetry in particular. This research deals with the dualism of white and black in the poetry of Antar and the relationship of this duality with the same poet. It may come to mind that the poet To ignore the mention of this duality in his poetry, but contrary to what the reader expected more than mentioned and talk about, and so he does not escape from the basic problem facing him in his life, a color node, but tries to address it and face to overcome Through its introduction and conform to religious, mythological and social standards and the same And moral values, by deconstructing this dualism and making black as well as white acceptable on both the personal and social levels. Through his poetic style and his good use of white and black, he attempts to modify the balance between his understanding and his society understands of human relations in accordance with humanitarian principles and not just formal forms in which society believes and gives them something of holiness.